Temperature effects on Xe bubble structure and grain boundary migration in UO2: A molecular dynamics simulation - Zhen Guo; Hui Ma; Danmin Peng; Hongwei Bao; Zhipeng Sun; Yong Xin; Jibin Zhang; Fei Ma (Journal of Materials Research and Technology)
The interaction between fission gas Xe and grain boundaries (GBs) in polycrystalline UO2 nuclear fuel is intricate at elevated temperatures. Herein, molecular dynamics simulations were employed to investigate the structural characteristics and evolution of intergranular and intragranular Xe bubbles in UO2. The results indicate that temperature elevating will significantly disorder the atomic structure and geometry of Xe bubbles, as a result, the pressure of Xe bubbles is lowered with expanded volume. Especially, the intergranular Xe bubbles are more sensitive to temperature and, generally, they suffer the higher pressure with the smaller volume, as compared to those of the intragranular Xe bubbles. The higher the temperature, the faster the migration of GBs. Consequently, at the lower temperature, GBs migrate at a lower migration rate, so that Xe atoms have enough time to diffuse into GBs when Xe bubbles meet GBs, while only part of Xe atoms are diffused into GBs at the higher temperature, and the residual Xe atoms are left behind GBs, with the bubble morphology changing from cluster-shaped into short-rod like. The elevated temperature and the Xe atoms diffused into GBs could promote the migration of GBs. However, the residual Xe bubble hinders the migration of GBs. Interestingly, reordering of the disrupted atomic structure occurs in Σ5b STGB, which might alter the shear-coupling factor β value from negative to positive, leading to an opposite migration of GBs at 1200 K or higher. The results are of significant guidance to understanding on Xe bubble structure and GB migration.